2020
DOI: 10.1111/are.14945
|View full text |Cite
|
Sign up to set email alerts
|

A temperature shift during embryogenesis impacts prevalence of deformity in diploid and triploid Atlantic salmon (Salmo salarL.)

Abstract: The study investigated the effects of a temperature shift during embryogenesis on diploid and triploid Atlantic salmon (Salmo salar L.) embryo development and juvenile skeletal deformities. From fertilization, sibling populations were incubated under one of three temperatures (6, 8 or 11°C) until 400 °days when all fish were then reared under a common temperature until smolt. Survival was negatively impacted by increasing temperatures irrespective of ploidy. There was no effect of incubation temperatures on gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 61 publications
0
4
1
Order By: Relevance
“…Our observed mortality did not deviate significantly from previous literature. Clarkson et al [14] reported a mortality of 16.4% ± 19.2% for diploids and 22.3% ± 21.9% for triploids from fertilisation to 400 DD at 6 °C, compared to 10.93% and 19.89%, respectively, for the current experiment. The reasons for the higher rate of mortality seen in triploids during embryogenesis are multifaceted.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…Our observed mortality did not deviate significantly from previous literature. Clarkson et al [14] reported a mortality of 16.4% ± 19.2% for diploids and 22.3% ± 21.9% for triploids from fertilisation to 400 DD at 6 °C, compared to 10.93% and 19.89%, respectively, for the current experiment. The reasons for the higher rate of mortality seen in triploids during embryogenesis are multifaceted.…”
Section: Discussioncontrasting
confidence: 38%
“…The reasons for the higher rate of mortality seen in triploids during embryogenesis are multifaceted. Triploids tend to suffer increased mortality at higher incubation temperatures [14,15]. Triploids also suffer from increased sensitivity to egg quality [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other experiments demonstrate that even when induction of triploidy is successful, chromosome aberrations are present that may affect gene expression (Glover et al 2020). Triploids appear to require a lower incubation temperature than the current industry standard of 8 °C (Clarkson et al 2021), thus temperature control is one way to minimise otherwise emergent deformities in triploids. Large triploid Atlantic salmon have been shown to perform better at colder water temperatures compared to diploids (Sambraus et al 2018).…”
Section: Other Non-target Speciesmentioning
confidence: 99%
“…Proper warming can stimulate the up-regulation of Col2a1 transcription level in cultured dedifferentiated chondrocytes in vitro and promote the redifferentiation of cartilage tissue (Ito et al, 2015). Studies in Atlantic salmon have shown that thermal stimulation during embryogenesis affects the expression of important developmental genes such as Col2a1, and this effect continues into subsequent development in fish (Clarkson et al, 2020). Ytteborg et al (2010a) showed that Col2a1 transcription decreased in Atlantic salmon reared at HT.…”
Section: Effects Of High Water Temperature On Genes Related To Chondrocyte Developmentmentioning
confidence: 99%